THE INTRODUCTION OF HIJAIYAH LETTERS IN SIGN LANGUAGES USING AUGMENTED REALITY TECHNOLOGY - Dewi Tresnawati; Rendi Algani; Syauqi Mubaraq (Informatika, Universitas Jenderal Soedirman, 2022)
The use of communication through sign language is generally carried out by someone who has a hearing barrier and communicates directly verbally, one of which is deaf and deaf. Deaf people have problems receiving information from the environment which results in less-than-optimal delivery of learning material so that it affects their learning achievement. One of them is the achievement in the field of Islam by recognizing hijaiyah letters. Therefore, we need a media that can optimize other senses, namely the sense of sight, one of which uses Augmented Reality technology. Making hijaiyah letter recognition learning applications using sign language with Augmented Reality technology which is expected to help deaf people in receiving material and teachers / teachers in delivering learning material. In this study, using the Multimedia Development Life Cycle research method, application testing uses the Alpha testing method with Black Box testing and Betta testing on user satisfaction. The test results 96% of respondents stated that the use of augmented reality technology helps in the learning process so that it can be a solution in tackling the problem of less than optimal acceptance of information from the environment so that it affects the learning achievement of people with speech deafness. Based on the test results 86.4% of users of the hijaiyah letter recognition application with the language used to assist in the learning process, especially the Koran lesson using the language of the manager.